Dynamiskt LED-system för växter - Dynamic LED Control System for Agriculture - Gybrant, Anton; Vigeliusson, Elliot; Amberg, Alexander; Thorsell, Theo; Peterson, Atle (My University, 2026)
This thesis focuses on the design and construction of a LED based lighting system for agricultural applications. The purpose is to develop a system that employs PWM dimming to adjust the spectral composition and intensity of the emitted light by changing the duty cycle with a microprocessor. This enables the spectral output of the lighting system to be controlled to meet the requirements of different plants. The goal is to achieve higher efficiency than current HPS-based lighting systems used in agriculture. The project encompasses the design and testing of a PCB used to drive and control a LED PCB. The prototype was constructed to allow both manual control of individual channels and automatic regulation via a PI controller that utilizes real-time input from an external light sensor. The results show that the efficacy of the system is nearly doubled that of a HPS based lighting system. The lighting system was able to produce a PPFD of 235 μmol/(m2s) with an intended light mix at the ratio 20:60:20 between blue, red and far-red light. At this PPFD, the blue and far-red light intensities could be increased by more than 100%, allowing substantial flexibility in spectral composition. With this light mix, the system had a calculated efficacy of 3.43 PPF/W, with up to 61% of the input power being translated into photosynthetically active light. Disregarding light mix, the maximum achievable PPFD of the system is 378 μmol/(m2s). Incorrect dimensioning of some LED driver components and suspected electromagnetic interference causes lower than intended ON current from the LED drivers. This results in the spectral output being less adjustable than intended. While the system can compensate for ambient light, the spectral sensor used is only capable of measuring relative light intensity and lacks the ability to measure absolute photon flux density. The control system is highly sensitive to positional changes of the spectral sensor. A calibration method was implemented to dynamically set the target based on the current sensor position. Electrical protection measures were successfully implemented into the design.
Keywords: Horticultural Lighting, LED Lighting, Spectral Sensing, Photosynthetic Photon Flux Density (PPFD), Lighting Control, Pulse Width Modulation (PWM), PI Regulator, DC–DC Converters, Peak Current Mode (PCM) Control.